Temperature-dependent resistance of a finite one-dimensional Josephson junction array - Engström, Klas; Kinaret, Jari M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
We study theoretically the temperature and array-length dependences of the resistance of a finite one-dimensional array of Josephson junctions. We use both analytic approximations and numerical simulations, and conclude that within the self-charging model, all finite arrays are resistive in the low-temperature limit. A heuristic analysis shows qualitative agreement with resistance obtained from Monte Carlo simulations, establishing a connection between resistance and the occurrence of vortices in the corresponding 1 +1D XY-model. We compare our results with recent experiments and conclude that while the self-charging model reproduces some of the experimental observations, it underestimates the superconducting tendencies in the experimental structures.